(untitled) (Fiep Bulletin - online, 2014)
CREF6/MG is primarily in charge of the enforcement, regulation and inspection of acts performed in the exercise of Physical Education, and no matter its great importance, it was not able to attend every professionals’ need, so Casa da Educação Física Institute was created at its shadow. The Casa da Educação Física has supported numerous activities related to the improvement of professionals in Minas Gerais and in Brazil to levels that would otherwise hardily be attained. We highlight the support to scientific publications, the financing expenses to have the presence of international names in Physical Education and Sports in Minas Gerais; the Paulo Roberto Bassolli Prize and the holding up of International Congresses.